Career Barriers for Chinese Immigrants in the United States. Issue 3 (September 2016) - Leong, Frederick T. L.; Tang, Mei
Abstract : To assist career counselors working with diverse populations, this article examines the career barriers experienced by Chinese immigrants in the United States. It begins with an overview of the history and background of Chinese immigrants. The rest of the article is based on an adapted ecological model for studying career barriers for Chinese immigrants that is an integration of Bogardus's (1933 ) social distance theory and Bronfenbrenner's (1977, 1979 ) ecological systems theory of human development. Career barriers are discussed along the multiple nested contexts at the societal, community, schools and colleges, and workplace levels. Within these contexts, career barriers range from ethnic stereotypes to unintended consequences of the model minority myth. Other barriers include language, lack of social support, and workplace discrimination. The article concludes with recommendations for overcoming these career barriers.